Time to beat the bugs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The sterile insect technique: an environmental-friendly method of insect pest suppression and eradication Video, by the Animal Production & Health Section of the joint FAO/IAEA Division. 28.5 minutes, in PAL, NTSC and SECAM and available for free to cou